Middle income countries? An alternative development taxonomy of Latin America and the Caribbean - TEZANOS VÁZQUEZ, Sergio; QUIÑONES MONTELLANO, Ainoa (Revista Iberoamericana de Estudios de Desarrollo, 2012)
Although it is not asy to classify countries according to their levels of development –mainly because the concept of “human development” is complex and multidimensional –, the most widespread classification is just the simplest one, based on income per capita levels. According to this classification, most of the Latin America and the Caribbean (LAC) countries are located in the world middle-income strata. This paper proposes an alternative “development taxonomy” for LAC middle-income countries. Using a cluster analysis we identify and characterize three groups of countries in relation to 10 main “development gaps”: the most advanced countries (Mexico, Chile, Argentina, Venezuela, Uruguay and Brasil), the middle-development countries (Panama, Costa Rica, Colombia, Jamaica, Dominican Republic, Ecuador, Peru, Belize, El Salvador, Paraguay and Guyana) and those countries with the greatest development challenges (Guatemala, Bolivia, Honduras and Nicaragua).